2015
DOI: 10.5296/ber.v5i2.8005
|View full text |Cite
|
Sign up to set email alerts
|

The 2012 US Presidential Election Polls And Stock Returns

Abstract: <p class="ber"><span lang="EN-GB">This study investigates the relationship between daily US presidential election poll results and stock returns. The sample consists of the daily presidential election polls published in the New-York Times for the period between May 31 and November 5, 2012. They include the percentage of support for the Democratic candidate, Barack Obama, and the Republican candidate, Mitt Romney. The findings indicate that stock returns are positively related to the poll results th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Two lines of research have been explored that provide context and suggest an explanation. Levy (2007; 2012) reports that the ideological messages the IDF offers all its conscripts are increasingly ethno-nationalist. This may explain the tendency among non-religious veterans to level off their attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two lines of research have been explored that provide context and suggest an explanation. Levy (2007; 2012) reports that the ideological messages the IDF offers all its conscripts are increasingly ethno-nationalist. This may explain the tendency among non-religious veterans to level off their attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent evidence has weakened the Israel Defense Forces' (IDF) reputation as the ultimate agent of socialization, exposing its role in the reproduction of existing ethno-social divides (Cohen 2008; Levy 2007). Nevertheless, failure to increase cohesiveness among veterans is seen as deleterious to the IDF experience, except for accommodating the religious needs of the Orthodox (Levy 2007; 2012), which is considered a special case. Here, the army and rabbinic authorities design programs dedicated to maintaining an environment that preserves the unique value system of the religious (Levy 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Valuation of entities associated with the Party increased by 0.17%. The impact of politics is also studied by Levy and Yagil (2015), who showed that each time the polls indicated the assumption of power by a liberal president, the income rates on the stock market increased.…”
mentioning
confidence: 99%